A modified T categorization for part-solid lesions in Chinese patients with clinical stage I Non–small cell lung cancer. (July 2020) - Deng, Jiajun; Zhao, Mengmeng; Wang, Tingting; She, Yunlang; Wu, Junqi; E, Haoran; Gao, Jiani; Sun, Xiwen; Jiang, Gening; Zhu, Yuming; Xie, Dong; Chen, Chang
Abstract: Objectives: We evaluated the prognostic impact of the presence of ground glass opacity (GGO) component and compared a modified clinical T categorization (cTm ) with the current 8th classification (cT8 ) for survival prediction in Chinese patients with clinical stage I non–small cell lung cancer (NSCLC). Methods: According to cTm and cT8 classifications, we retrospectively evaluated 1461 patients with part-solid or pure-solid lesions. The recurrence-free survival (RFS) and overall survival (OS) were analyzed by Kaplan-Meier method and Cox proportional hazard model. The concordance index (C- index), reclassification improvement (NRI), integrated discrimination improvement (IDI), and decision curve analysis (DCA) were performed to estimate reclassification net benefits of cTm for survival prediction. Results: The cT8 classification clearly stratifies the survival outcomes in solid tumors but not in part-solid tumors. The presence of GGO components was an independent prognostic factor for both RFS and OS (p < 0.001), indicating a better outcome in each clinical T stage. The C-index was significantly improved from 0.650 to 0.730 for RFS (p < 0.001) and 0.647 to 0.730 for OS (p < 0.001) after reclassifying by cTm categorization. The DCA, NRI (RFS: 0.342, OS: 0.302), and IDI (RFS: 0.070, OS: 0.054) demonstrated that the cTm classification provided more net benefit in the survival prediction compared with the current cT8 classification. Conclusions: The current cT8 classification may not be appropriate for part-solid lesions because the presence of GGO components is associated with excellent prognosis despite clinical stage. Also, the cTm classification for part-solid lesions showed an improvement in survival prediction.